(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
The article discusses the features of Internet communication, which is becoming increasingly important in the modern communicative space. It is noted that communication on the Internet has its own characteristics, which are manifested at all levels of communication and are reflected in all components of the communication situation: addressee, addressee, communication channel, encoding and decoding information, communication barriers, etc. A diagram of the communication situation is built, which is described in relation to Internet communication. Particular attention is paid to the language as a component of the Internet communication situation. It is noted that it not only develops on the verge of oral and written forms of speech, but also reflects all the most significant and relevant trends in modern language development, demonstrates the creative potential of communicators.